Planning for pharmacy health information technology in critical access hospitals. - Hartzema AG; Winterstein AG; Johns TE; De Leon JM; Bailey W; McDonald K; Pannell R (American Journal of Health-System Pharmacy, 2007)
PURPOSE: A plan for the implementation of medication-related health information technology (HIT) in 12 critical access hospitals (CAHs) to improve safety and reduce medication errors is described. SUMMARY: Interviews were conducted to assess the status of HIT in 12 CAHs, including HIT needs and desires and barriers to HIT adoption. Two conferences were held as part of the planning process. It was determined that pharmacy HIT (pHIT) should be implemented in three phases in the CAHs. In phase 1, it was found that the first HIT needed by the CAHs was pharmacy information management systems (PIMS), the cornerstone for the implementation of other HITs. Criteria were developed for the appropriate selection of PIMS for the CAHs. Phase 2 revealed that automated dispensing cabinets (ADCs) should be the next HIT implementation. ADCs are effective in the reduction of medication errors in the dispensing stage. Phase 3 dealt with the implementation of smart infusion pumps. Smart infusion pumps contain a standard data set that includes parameters for infusion fluids and a clinical decision-support system, and they keep a record of rule violations. Barriers to HIT implementation included funding, staff resistance to change, staff adaptation to HIT and workflow changes, time constraints on small sta., facility and building barriers, and lack of information technology support. CONCLUSION: Planning conferences and interviews with hospital representatives helped to identify the HIT needs of 12 CAHs. The planning process resulted in a three-phase plan for pHIT implementation, which will include PIMS, ADCs, and smart infusion pumps.